Object-Moving Robot Arm based on Color - Sengsalong, Areepen; Satya Widodo, Nuryono (Signal and Image Processing Letters, 2019)
The aim of this research is to make a robot arm moving objects based on color using 2 servo motors and 6 light photodiode sensors integrated with the Arduino Mega 2560 microcontroller.  The light photodiode sensor is used to detect red, green and blue colors. This system is equipped with an LCD to display the output of the Arduino Mega 2560 which is a notice of the color detected. The process of moving objects based on color is simulated using 3 colored objects namely red, green, and blue. The robot arm gripper will move to pick and move objects based on color, when the light photodiode sensor detects a color input. Based on system testing, overall the robot arm is functioning properly, i.e. it shows that the robot arm is able to move objects automatically with large test results obtained by 0°, 40°, 60°, 90°, and 120°. Whereas for sensor testing the value of red is 400, the value of green is 150, and the value of blue is 600.